2024
DOI: 10.1101/2024.04.29.24306564
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A microbiota-directed complementary food intervention in 12-18-month-old Bangladeshi children improves linear growth

Ishita Mostafa,
Matthew C. Hibberd,
Steven J. Hartman
et al.

Abstract: Background Globally, stunting affects ~150 million children under five, while wasting affects nearly 50 million. Current interventions have had limited effectiveness in ameliorating long-term sequelae of undernutrition including stunting, cognitive deficits and immune dysfunction. Disrupted development of the gut microbiota has been linked to the pathogenesis of undernutrition, providing potentially new treatment approaches. Methods 124 Bangladeshi children with moderate acute malnutrition (MAM) enrolled (at 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…In both studies, though wasting was frequently accompanied by stunting, MDCF-2 did not produce a statistically significant effect on LAZ compared to RUSF during the 3-month intervention period. However, MDCF-2 led to a significant improvement in linear growth trajectories of children with primary MAM in the subsequent 2-year period of follow-up ( 8 ); this effect was foreshadowed by increased levels of plasma proteomic biomarkers and mediators of musculoskeletal development at the end of the treatment phase. Longer periods of intervention and/or more extended post-treatment follow-up will be needed to determine whether stunting, and/or neurodevelopmental abnormalities, are ameliorated by MDCF-2 in children with post-SAM MAM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In both studies, though wasting was frequently accompanied by stunting, MDCF-2 did not produce a statistically significant effect on LAZ compared to RUSF during the 3-month intervention period. However, MDCF-2 led to a significant improvement in linear growth trajectories of children with primary MAM in the subsequent 2-year period of follow-up ( 8 ); this effect was foreshadowed by increased levels of plasma proteomic biomarkers and mediators of musculoskeletal development at the end of the treatment phase. Longer periods of intervention and/or more extended post-treatment follow-up will be needed to determine whether stunting, and/or neurodevelopmental abnormalities, are ameliorated by MDCF-2 in children with post-SAM MAM.…”
Section: Discussionmentioning
confidence: 99%
“…MDCF-2 contained four complementary food components (chickpea flour, soybean flour, peanut paste, green banana) plus soybean oil, sugar and micronutrients ( 3, 7 ). The superior effect of MDCF-2 on β-WLZ was accompanied by more complete microbiota repair plus greater increases in levels of plasma protein mediators and biomarkers of musculoskeletal and central nervous system (CNS) development at the end of treatment ( 7 ) and a significant improvement in linear growth trajectories in the 2-year period after cessation of treatment ( 8 ). Shotgun sequencing of DNA isolated from fecal biospecimens serially collected during this trial identified 75 bacterial metagenome assembled genomes (MAGs) whose abundances were significantly positively associated with WLZ and whose genomes were enriched for metabolic pathways involved in utilization of plant polysaccharides ( 9 ).…”
Section: Introductionmentioning
confidence: 99%